Twenty-three women officers’ experiences of policing in England: The same old story or a different story? - Cunningham, Emma (International journal of police science & management, 2020)
Our research project was concerned primarily with using a feminist analysis to explore the lived reality of 23 women police officers in England and Wales. We undertook 23 qualitative interviews with our participants and our research straddles four decades of policing practice, which allowed us to explore changes that were seen to have taken place during this period. First, participants discussed their lived reality, which included banter, bullying and harassment for many. Second, and perhaps more surprisingly, at certain times of unrest, riots or threats, some of our participants were provided with opportunities, for example, during the IRA threat, the riot in Toxteth and the miners’ strike. We suggest that examples from our data capture an early disruption of the ‘ideal’ heroic male police officer that Silvestri examines [Silvestri M (2018) Disrupting the ‘heroic’ male within policing: a case of direct entry. Feminist Criminology 13(3): 309-328] whose removal from their normal role during periods of socio-political disorder allowed women officers to leave the gendered division of labour and undertake the heroic police constable role while the men were busy being ‘heroic’ at the source of threat and unrest. We sought to explore changes such as the uniform as a site of protest for some of our officers who challenged an uncomfortable and unfit uniform in the early days, and explained that there were still problems with the kit and design at times. Our findings illustrated that, on the whole, although massive changes had been made, it was a case of the same old story in terms of sexual harassment and banter for female officers and more was required to address these issues, which fits with reviews and studies in both England and Wales and in Australia. Finally, we noted using participants’ words how much many of these women had enjoyed their role within policing in spite of these challenges.